Methods used by psychologists for identifying dyslexia: A systematic review. (20th December 2021) - Sadusky, Andrea; Berger, Emily P.; Reupert, Andrea E.; Freeman, Nerelie C.
Abstract : Inconsistencies in the operationalisation of dyslexia in assessment practices are concerning. Variations in different countries' education contexts and education‐related legislation could contribute to continuing discrepancies between psychologists' assessment practices. However, an international "snapshot" of these practices is unavailable. An international comparison of psychologists' dyslexia assessment practices could help ascertain whether there are contextual factors that can foster converging practices. Accordingly, this study systematically reviewed the literature to capture how psychologists identify and/or diagnose dyslexia across English‐speaking countries. Quantitative and/or qualitative studies, published between 2013 and 2021, that investigated psychologists' self‐reported methods for assessing, identifying, and/or diagnosing individuals with dyslexia were included. Eleven studies (published across fourteen papers) met the inclusion criteria. Most included studies sampled school psychologists who work in the USA. Psychologists' dyslexia assessment practices were diverse (including the use of cognitive discrepancy and response‐to‐intervention methods). The results highlight an international need to develop a consensus operational definition of dyslexia and universal assessment guidelines. Future research might investigate the practices and beliefs of psychologists who work outside of the USA, and to be inclusive of adult populations. Implications for research and training are explored.